Uterine infusion of bacteria alters the transcriptome of bovine oocytes. Issue 8 (16th July 2020) - Piersanti, Rachel L.; Block, Jeremy; Ma, Zhengxin; Jeong, KwangCheol C.; Santos, José E. P.; Yu, Fahong; Sheldon, I. Martin; Bromfield, John J.
Abstract: Postpartum uterine infection reduces fertility in dairy cattle; however, the mechanisms of uterine infection‐mediated infertility are unknown. Paradoxically, infection‐induced infertility persists after the resolution of disease. Oocytes are a finite resource, which are present at various stages of development during uterine infection. It is likely that oocyte development is influenced by uterine infection‐induced changes to the follicular microenvironment. To better understand the impact of infection on oocyte quality we employed global transcriptomics of oocytes collected from heifers after receiving intrauterine infusion of pathogenic Escherichia coli and Trueperella pyogenes . We hypothesized that the oocyte transcriptome would be altered in response to intrauterine infection. A total of 452 differentially expressed genes were identified in oocytes collected from heifers 4 days after bacteria infusion compared to vehicle infusion, while 539 differentially expressed genes were identified in oocytes collected from heifers 60 days after bacteria infusion. Only 42 genes were differentially expressed in bacteria‐infused heifers at both Day 4 and Day 60. Interferon, HMGB1, ILK, IL‐6, and TGF‐beta signaling pathways were downregulated in oocytes collected at Day 4 from bacteria‐infused heifers, while interferon, ILK, and IL‐6 signaling were upregulated in oocytes collected at Day 60 from bacteria‐infused heifers. These data suggest that bacterial infusion alters the oocyte transcriptome differently at Day 4 and Day 60, suggesting different follicle stages are susceptible to damage. Characterizing the long‐term impacts of uterine infection on the oocyte transcriptome aids in our understanding of how infection causes infertility in dairy cattle.